Pola dan Fungsi Akronim Bahasa Gaul Siswa SMK Muhammadiyah 8 Siliragung dalam Komunikasi WA - Cici Arista; Hari Windu Asrini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the patterns and communicative functions of slang acronyms used by students of SMK Muhammadiyah 8 Siliragung in WhatsApp communication. The research employs a descriptive qualitative approach.The data were obtained from students’ WhatsApp group conversations and collected through observation, reading, note-taking, and documentation techniques. The date were then analyzed based on morphological theory, particularly acronym formation, and the language function theory proposed by Roman Jakobson. The findings indicate that slang acronyms used by students are formed through several systematic patterns, including the retention of initial letters or syllables, the combination of syllables and letters, the selection of specific syllables with phonological modification, and word truncation. Although non-standard, these acronyms still adhere to Indonesian phonotactic principles, making them pronounceable and comprehensible within the speech community. Furthermore, the analysis of language functions reveals that the acronyms perform various communicative functions, namely conative, emotive, referential, and poetic functions. Among these, conative and emotive functions are the most dominant, as acronyms are frequently used to express commands, invitations, emotions, and personal attitudes in informal digital interactions. The referential and poetic functions demonstrate that acronyms also serve to convey information and create humorous or aesthetic effects. Overall, the use of slang acronyms reflects students’ linguistic creativity and social identity in digital communication, contributing to the study of morphology and pragmatics in contemporary Indonesian language use.